Development and evaluation of acceptance of a web based education module for reducing risk of mild cognitive impairment among older adults - Divya Vanoh; Suzana Shahar; Intan Hafizah Mohd Ishak; Zahara Abdul Manaf; Rosdinom Razali; Nazlena Mohd Ali; Shahrul Mohd Noah (Penerbit Universiti Kebangsaan Malaysia, 2018)
Relatively less comprehensive web based programme has been developed for detecting risk of mild cognitive impairment (MCI) and further impart preventive strategies and lifestyle education. Thus, this study has developed a comprehensive web based programme for early screening of risk of MCI together with education package for preventing MCI known as WESIHAT 2.0. WESIHAT 2.0 is a senior friendly website which has appropriate design interface facilitating access of older people especially with the use of touch-screen technology. WESIHAT 2.0 has incorporated four major components namely TUA WELLNESS screening tool, which is a comprehensive, online based, 10-item screening tool for detecting risk of MCI, 10-guides for preventing MCI, health diary and healthy food. Evaluation of acceptance of WESIHAT 2.0 was done among 71 people which comprised of 30 older people and 30 caregivers, chosen equally based on ethnic composition and 11 health care professionals who has experience working in the field of geriatric and 2 freelance website developer. All older people and caregivers stated that the content of website was very useful for preventing MCI, however, about 36.4% of health professionals stated several improvements needed to be done before releasing the end-product to the users. Comments given were smaller font size (27.3), addition of more pictures (27.3%), using simpler terms (36.4%) and changing certain design for better view of older people (18.2%). Amendments were made based on each comment given and the finalized website were used for a 6-month intervention programme for neuroprotection among older people who failed to achieve successful aging. It is timely for an online based approach for prevention of MCI. WESIHAT 2.0 is the first website in Malaysia which has been accepted by all older people and caregiver and more than half of healthcare professionals to prevent memory decline.